Using Photography to Assess Foods Offered to Preschoolers in Parent Packed Lunches (P11-069-19) - Hobbs, Savannah (Curr Dev Nutr, 2019)
OBJECTIVES: To examine the quality of meals offered to children ages 3–5 years in parent packed lunches at a university-based early childhood center. METHODS: Using a protocol based on the Remote Food Photography Method, trained research staff used iPads to take before and after photos of preschoolers’ packed lunches over 1 week. Meal quality was assessed using the Healthy Meal Index (HMI) and Child and Adult Food Care Program (CACFP) standards. Photos were independently coded by 2 researchers for key meal details, including availability and type of fruits, vegetables, grains, proteins and dairy, which fed into established scoring criteria to generate a HMI adequacy score. The mean HMI adequacy score for all lunches and percentages of lunches containing each adequacy food group were calculated to assess total meal quality. Photos were also reviewed using CACFP standards for availability, type, and amount of foods offered. Researchers coded photos (k = .86) for the inclusion of 4 food groups (fruits, vegetables, grains, and protein; milk was not served), and serving sizes were visually estimated and compared with recommended CACFP serving sizes: 1.5 oz of protein and 0.25 c each of fruits, vegetables, and grains. Mean standardized servings offered to children were calculated from these standards. RESULTS: Lunches (n = 301) from 79 children were photographed (2-5 days/child). The mean HMI adequacy score was [Formula: see text]  = 37.7 11.0 (out of 65), with a range of 15.0 to 65.0. For all meals, 89% contained a grain, 86% contained fruit, 75% contained dairy (non-milk), 60% contained protein, and 48% contained a vegetable. Compared to CACFP standards, lunches had an average of 2.77 0.78 food groups present out of 4. Standardized servings offered for grains ([Formula: see text]  = 2.60 ± 1.49), fruits ([Formula: see text]  = 1.89 ± 1.09), protein ([Formula: see text]  = 1.42 ± .68), and vegetables ([Formula: see text]  = 1.35 ± .74) were high when calculated based on recommended CACFP serving sizes. CONCLUSIONS: In this study, parent packed lunches fell short of meeting CACFP guidelines by offering less than 3 of the recommended 4 food groups, with a large percentage of lunches containing grains, fruits, and dairy. Children were provided with larger amounts than recommended for all food groups, particularly for grains. FUNDING SOURCES: Colorado State University Health Behaviors Lab.